AReview onComparison betweenShell And Tube Heat Exchanger And Helical Coil Heat Exchanger - NamrataD. Ranaware; KrishnatN. Molawade; Prof. L. N. Mane (International Journal of Innovations in Engineering Research and Technology, 2021)
The curved shape of the tube causes the flowing fluid to experience centrifugal force. The extent of centrifugal force experienced depends on the local axial velocity of the fluid particle and radius of curvature of the coil. The fluid particles flowing at the core of the pipe have higher velocities than those flowing near to the pipe wall. Thus the fluid particles flowing close to the tube wall experience a lower centrifugal force than the fluid particles flowing in the tube core. This causes the fluid from the core region to be pushed towards the outer wall. This stream bifurcates at the wall and drives the fluid towards the inner wall along the tube periphery, causing generation of counter-rotating vortices called secondary flows whichproduce additional transport of the fluid over the cross section of the pipe. This additional convective transport increases heat transfer and the pressure drop when compared to that in a straight tube